Information Technology Risk Analysis and Mitigation Using ISO 31000 and House of Risk (HOR) for SIAK in Western Seram Regency - Christine Pentury; Johan Jimmy Carter Tambotoh (Politeknik Negeri Madiun, 2022)
SIAK stands for population administration information system. It is a computerized system that was established according to administrative service regulations to organize the population administration system in Indonesia, more precisely in the Western Seram Regency. Given the critical function of this application in aiding in identifying regional demographic statistics, it is vital to examine potential dangers while also identifying mitigation measures that may be performed to avoid them. ISO 31000 was utilized in the study to map potential hazards for subsequent reduction using the House of Risk (HOR) methodology. According to the findings of this research, there is one danger that falls into the high category, namely the unstable network. Additionally, based on the results of risk mitigation identification, two mitigation steps are identified that can mitigate 60% of existing risks, namely the construction particular resistant to natural disasters for critical equipment storage and collaboration with internet providers to ensure stable internet and network connections.